Stakeholder models, sustainability and the ethics of planned obsolescence - Matisonn, Joanne Rona (My University, 2016)
In this research report I will be investigating whether companies have an obligation to shareholders or a wider group of stakeholders. If they have an obligation to a wider group of stakeholders, then the question is whether planned obsolescence is an ethical practice that should inform their business and what the role is of ethical leaders in addressing problems such as job losses, environmental damage and conspicuous consumption that result from planned obsolescence. As part of my attempt to answer the research question I will discuss the evolution of views regarding business and the profit motive in relation to shareholders, the multi-fiduciary model, the enlightened shareholder approach and the inclusive stakeholder approach. I will then focus on planned obsolescence as a pervasive business practice and what circumstances morally justify negative consequences which are weighed against the positive effects. Finally, I will propose ethical solutions to the issues raised around planned obsolescence, aimed at achieving specific benefits whilst also limiting the negativity introduced by planned obsolescence.
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Arts, Applied Ethics for Professionals Johannesburg, 2016
Keywords: Stockholders; Corporate governance; Depreciation; Ethics